Encyclopedia of Caribbean Archaeology - Gilmore, Richard Grant, 1947-; Reid, Basil A., 1961- (Book collections on Project MUSE., 2014)
Encyclopedia of Caribbean Archaeology offers a comprehensive overview of the available archaeological research conducted in the region. Beginning with the earliest native migrations and moving through contemporary issues of heritage management, the contributors tackle the usual questions of colonization, adaptation, and evolution while embracing newer research techniques, such as geoinformatics, archaeometry, paleodemography, DNA analysis, and seafaring simulations. Entries are cross-referenced so that readers can efficiently access data on a variety of related topics. The introduction incl.